Efficacy, Complications and Effects of Alcides Pereira’s Sutures in the Management of Uterine Atony: A Retrospective Study - Beatriz Cordeiro Féria; Patrícia Nazaré; Joana Figueiredo; Inês Neves Gomes; Alcides Pereira (Acta Médica Portuguesa, 2024)
Introduction: Uterine compressive sutures are conservative measures applied in cases of severe postpartum hemorrhage unresponsive to uterotonics. Pereira’s suture was introduced in 2005 and consists of two longitudinal and three transverse non-transfixes sutures. Previous studies reported favorable results, highlighting its benefits and value. The aim of this study was to assess the efficacy, complications, and impact on fertility and future pregnancies of Pereira’s suture applied in cases of uterine atony and postpartum hemorrhage. Methods: An observational retrospective study was performed by consulting the medical records of women treated with Pereira’s compressive sutures in a tertiary center between January 2013 and December 2022. We registered demographic data, pregnancy outcomes, short-term complications, and outcomes of subsequent pregnancies. Results: A total of 50 women were treated with Pereira’s suture. The overall success rate was 96% and no hysterectomies were performed. Women who had sutures performed during an intra-cesarean section had better outcomes than those who had an after-cesarean section. Complications were reported in 12% (n = 6) of women, with the most frequent being pelvic infection (n = 3) and abdominal pain (n = 3). Regarding fertility, all women desiring a future pregnancy (n = 5) were able to conceive, resulting in three live births. Conclusion: Pereira’s suture is a type of suture that provides numerous advantages and should be considered when first-line medical treatment fails. When applied at an early stage, the sutures may prevent maternal morbidity. The Alcides Pereira’s suture is a safe technique and appears to preserve fertility.